2019
DOI: 10.18805/lr-4117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Some Biopesticides against Helicoverpa Armigera (Hubner) in Pigeonpea under Natural Condition

Abstract: The field experiments on efficacy of some biopesticides against H. armigera on pigeonpea under field condition was carried out in the experimental field of department of Entomology at International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) Hyderabad, during 2016-2017 and 2017-2018.These studies revealed Spinosad 45 SC treatment as the most effective against H. armigera. Lower larval population of H. armigera was observed when crop was treated with consortia of biopesticides which was at par … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Among all treatments, Emamectin benzoate 5% SG (9.03%) was found significantly superior among all the treatments which are in line with the similar findings of Akhtar et al [8] with (10.4% and 11.9%) and Upadhyay et al [9] with (7.33%) and Dadas et al ( 2019) with (8.33%). Spinosad 45% SC (10.57%) is the next best treatment for reducing the population of pod borer which is in line with the similar findings of Dadas et al ( 2019) with (7.33%), Agale et al [10] with pooled mean percent (6.82%), Mihretie et al [11] with (11.39%), Akthar et al [8] with (7.8%). It is followed by NSKE+HaNPV+Bt (12.00%) which is in line with the similar finding of Byrappa et al [12] with (15.96%), Beauveria bassiana 1.5% SG (13.98%) which is in line with the similar finding of Singh et al [13] and Khorasiya et al [7] with (9.8%), and NSKE 5% (16.41%), Bacillus thuringiensis 4% WSP (12.00%) which is in line with the similar finding of Khorasiya et al [7] and Meena et al [14] with (13.17% and 10.50%) followed by Neem oil 2% (17.32%) which is in line with the similar finding of Abhilasha and Shekarappa [15] and Mishra et al [16] with (25.68%) which is less effective against pod borer.…”
Section: Resultssupporting
confidence: 82%
“…Among all treatments, Emamectin benzoate 5% SG (9.03%) was found significantly superior among all the treatments which are in line with the similar findings of Akhtar et al [8] with (10.4% and 11.9%) and Upadhyay et al [9] with (7.33%) and Dadas et al ( 2019) with (8.33%). Spinosad 45% SC (10.57%) is the next best treatment for reducing the population of pod borer which is in line with the similar findings of Dadas et al ( 2019) with (7.33%), Agale et al [10] with pooled mean percent (6.82%), Mihretie et al [11] with (11.39%), Akthar et al [8] with (7.8%). It is followed by NSKE+HaNPV+Bt (12.00%) which is in line with the similar finding of Byrappa et al [12] with (15.96%), Beauveria bassiana 1.5% SG (13.98%) which is in line with the similar finding of Singh et al [13] and Khorasiya et al [7] with (9.8%), and NSKE 5% (16.41%), Bacillus thuringiensis 4% WSP (12.00%) which is in line with the similar finding of Khorasiya et al [7] and Meena et al [14] with (13.17% and 10.50%) followed by Neem oil 2% (17.32%) which is in line with the similar finding of Abhilasha and Shekarappa [15] and Mishra et al [16] with (25.68%) which is less effective against pod borer.…”
Section: Resultssupporting
confidence: 82%
“…The maximum reduction 73.42 per cent recorded in spinosad 0.01 per cent treated plots. Agale et al (2021) reported that spinosad 45 SC was most effective against H. armigera in pigeonpea. The next effective treatment was indoxacarb 0.01 per cent (71.39 per cent reduction) followed by fipronil 0.01 per cent (70.12 per cent reduction) which were at par with each other.…”
Section: First Spray Of Insecticides and Biopesticidesmentioning
confidence: 99%
“…The studies and investigations for alternative pest management strategies in general and for H. armigera in particular is an ongoing process. The use of biopesticides (Agale et al, 2021), botanical and semiochemicals (Edosa, 2019) and our present study using azasteroids could be explored as one of the futuristic approaches for pest management. Therefore, such studies with azasteroids and similar compounds along with field validations can open avenues to be exploited for safe pest management technologies.…”
Section: Resultsmentioning
confidence: 91%